Database resources of the National Center for Biotechnology Information - Sayers, Eric W; Beck, Jeff; Brister, J Rodney; Bolton, Evan E; Canese, Kathi; Comeau, Donald C; Funk, Kathryn; Ketter, Anne; Kim, Sunghwan; Kimchi, Avi; Kitts, Paul A; Kuznetsov, Anatoliy; et al. (Nucleic acids research, 2020)
Abstract The National Center for Biotechnology Information (NCBI) provides a large suite of online resources for biological information and data, including the GenBank® nucleic acid sequence database and the PubMed database of citations and abstracts published in life science journals. The Entrez system provides search and retrieval operations for most of these data from 35 distinct databases. The E-utilities serve as the programming interface for the Entrez system. Custom implementations of the BLAST program provide sequence-based searching of many specialized datasets. New resources released in the past year include a new PubMed interface, a sequence database search and a gene orthologs page. Additional resources that were updated in the past year include PMC, Bookshelf, My Bibliography, Assembly, RefSeq, viral genomes, the prokaryotic genome annotation pipeline, Genome Workbench, dbSNP, BLAST, Primer-BLAST, IgBLAST and PubChem. All of these resources can be accessed through the NCBI home page at www.ncbi.nlm.nih.gov.